Dessorção de metais da alga marinha Sargassum filipendula - Seolatto, Araceli Aparecida (2008)
The main objective of this work was to accomplish a desorption study of the nickel, zinc and chromium metals of the Sargassum filipendula biomass. Four eluents were used (HCl, H2SO4, CaCl2, MgSO4, the last two in pH 3) in batch system, with groups of factorial design 4.23. The charge of metallic ion, eluent initial concentration and solid-liquid ratio were analyzed. The two analyzed answers were the amount desorbed and the weight loss during the desorption process. Two desorption systems were tested in column, the first operated with the direct passage and the second with the eluent recirculation. Soon afterwards, to evaluate the desorption effects in subsequent biosorption cycles, synthetic efluents composed individually of nickel, zinc, chrome and of the binary mixture (zinc and nickel) and ternary (nickel, zinc and chrome) were submitted to consecutive biosorption-desorption cycles in fixed-bed columns in recirculation system. The rupture and desorption curves were adjusted by the Bohart and Adams and Tan and Liou models, solved analytically, and by a numeric method that consider the axial dispersion and diffusion intraparticle. Soon afterwards, biosorption-desorption tests were accomplished with real effluents of galvanoplasty industries with the same procedure used for the synthetic ones. The results showed that all the factors were significant in the answers analyzed: desorption efficiency and weight loss in batch. Besides, several interactions among the factors were shown significant. Analyzing the contribution of each factor, it was verified that the best operational conditions in the nickel and zinc desoprtion were obtained for the eluents H2SO4 and MgSO4, in the largest concentration, larger metal charge and smaller solid-liquid ratio tested. The biomass desorption efficiency was shown superior to 95% in batch and 97% in the fixed-bed columns, respectively.At the end of the tenth cycle, it was verified that Sargassum filipendula seaweed continued presenting high biosorption values of these metals in solution, although the weight loss in the first desorption cycle was presented high values, that it was confirmed by the analyses of total organic carbon, in the eluent tanks, and the infra-red spectroscopy, in the used biomass. For the chrome desorption, it was possible to reach a maximum capacity of dessorção around 60%, Besides, the results of the subsequent biosorption stages were affected and there was a considerable efficiency reduction. The method of Bohart and Adams was shown efficient to modeling the experimental biosorpion data, while in the desorption, the best results were obtained with the mathematical model of numeric solution. In the tests realized with real effluents, composed by nickel and zinc, it was verified that the desorption were also came efficient and it provided the biomass utilization in 10 biosorption-desorption cycles, removing about 7 times more metal, that if the biomass had just been used once. Using the desorption process it was possible to use a smaller biomass amount, generating smaller residue amount, in case to come to be disposed in industrial embankments. Besides, the costs calculation of the materials used, showed that the costs with biomass regeneration by metals desorptions, for the nickel and zinc, regenerating with H2SO4 0,1 M was smaller than if the biomass had been to be changed in each biosorption stage. With obtained results, it was conclude that desorption can come as an efficient alternative in the biomass regeneration, used in the wastewater treatments, containing nickel and zinc. The desorption process was shown efficient in all of the accomplished stages, and it was possible to remove great amounts of metal with a smaller biomass amount. The process of nickel and zinc desorption presented a low cost, besides having facilitated the treatment process that spared successive biomass changes.